Effectiveness of vaccination against SARS-CoV-2 Omicron variant infection, symptomatic disease, and hospitalization: a systematic review and meta-analysis - Meggiolaro, Angela; Sane Schepisi, Monica; Farina, Sara; Castagna, Carolina; Mammone, Alessia; Siddu, Andrea; Stefanelli, Paola; Boccia, Stefania; Rezza, Giovanni (Expert review of vaccines, 2022)
This meta-analysis aims to assess the effectiveness of the current Sars-Cov2 vaccine regimens against Omicron infection. A secondary endpoint aims to investigate the waning effectiveness of primary vaccination against symptomatic infection and related hospitalization. The systematic review started on 1 December 2021 and was concluded on 1 March 2022. Random-effects frequentist meta-analyses and multiple meta-regressions were performed. In total, 15 studies are included in the quantitative synthesis. According to the meta-analysis results, the overall risk of Sars-Cov2 infection in vaccinated individuals is on average 31 · 5% lower than the infection risk in unvaccinated while vaccinated with one booster dose have a 70 · 4% risk reduction of Omicron infection compared to unvaccinated. In particular, one booster dose significantly decreases by 69% the risk of symptomatic Omicron infection with respect to unvaccinated. Six months after the primary vaccination, the average risk reduction declines to 22% against symptomatic infection and to 55% against hospitalization. Primary vaccination does not provide sufficient protection against symptomatic Omicron infection. Although the effectiveness of the primary vaccination against hospitalization due to Omicron remains significantly above 50% after 3 months, it dramatically fades after 6 months.